2008
DOI: 10.1021/ie800887v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Modeling of Free-Radical Batch Polymerization of Nonionized Methacrylic Acid in Aqueous Solution

Abstract: The batch free-radical polymerization of nonionized methacrylic acid (MAA) in aqueous solution has been investigated at 50 °C and initial monomer concentrations up to 30 wt % MAA. The rate of conversion increases as the initial weight fraction of MAA decreases, a result explained by the dependence of the propagation rate coefficient, k p , on monomer concentration. The conversion profiles measured at different MAA and initiator levels are represented by a polymerization model with conversion-dependent k p take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 34 publications
(76 reference statements)
4
75
1
1
Order By: Relevance
“…After about 60 min, an increase of the slope is noticeable, which is a sign of diffusion limitations to termination (gel effect). This is fully consistent with the experimental results of Buback et al [23], who ran their reactions at larger initiator concentrations (5 mmol/L, equivalent to ca. 0.12 wt %).…”
Section: Non-ionized Systemsupporting
confidence: 92%
See 2 more Smart Citations
“…After about 60 min, an increase of the slope is noticeable, which is a sign of diffusion limitations to termination (gel effect). This is fully consistent with the experimental results of Buback et al [23], who ran their reactions at larger initiator concentrations (5 mmol/L, equivalent to ca. 0.12 wt %).…”
Section: Non-ionized Systemsupporting
confidence: 92%
“…For the repetition of the reaction with 10 wt % MAA ( Figure S4), the difference in the slope above 40% conversion is a bit larger. Since this discrepancy (of similar size) at the same reaction conditions has already been reported in the literature [23], we consider this accuracy to be sufficient. A kinetic model suitable for evaluating the reaction rate and number average molecular weight of the active chains has been developed.…”
Section: Non-ionized Systemsupporting
confidence: 65%
See 1 more Smart Citation
“…The effect of the solids content on the conversion indicates that the dependence of the polymerization rate on the monomer conversion is not first order for any of the two monomers. This has been reported for the aqueous solution homopolymerization of MAA [19][20][21]25,42]. It has been found that the propagation rate coefficient of MAA was a function of the concentration of the monomer in the aqueous phase and of the ionization degree.…”
Section: Maa-co-pegma5 (5 Ethylene Glycol Units)mentioning
confidence: 55%
“…In addition to the effect of the monomer concentration on the k p , the ionization degree also affects the kinetics of acidic water-soluble monomers like AA and MAA. For instance, for MAA, one of the monomers used in this work, Lacík et al [19][20][21]25] have determined the effect of the ionization degree (from non-ionized to fully ionized conditions) and found that the k p significantly reduces on going from non-ionized form to the fully ionized form, and that this decrease diminishes as MAA concentration increases.…”
Section: Introductionmentioning
confidence: 98%